2022
DOI: 10.3390/antiox11081474
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Phytochemical Fingerprint of Two Diverse Phaseolus vulgarisvar. Tondino del Tavo and Cannellino Bio Extracts

Abstract: Common bean (Phaseolus vulgaris) represents one of the most famous foods with antiobesity activity showing a significant efficacy against fat accumulation, insulin resistance and dyslipidaemia. In this work, two Italian varieties of common bean, i.e., Tondino del Tavo and Cannellino Bio, from the centre of Italy were studied to characterise their phenolic profile by HPLC-PDA in relation to different fractions after a straightforward extraction procedure. Antioxidant property and enzymatic inhibition power were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…By performing different antioxidant assays such as ABTS, DPPH, and H2O2, the best antioxidant results were examined based on their comparative effectiveness. It may be due to the nature of these radicals that the apparent differences exist (the ABTS assay is assumed to be both hydrophilic and lipophilic antioxidant systems, while DPPH is only for hydrophobic systems) [5] . Hence, various biological antioxidant assays were conducted to test the efficacy of biological active compounds found in chloroform and ethyl acetate fractions by comparing the results of DPPH, ABTS, H2O2 free radical scavenging activity upon the basis of the compounds nature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By performing different antioxidant assays such as ABTS, DPPH, and H2O2, the best antioxidant results were examined based on their comparative effectiveness. It may be due to the nature of these radicals that the apparent differences exist (the ABTS assay is assumed to be both hydrophilic and lipophilic antioxidant systems, while DPPH is only for hydrophobic systems) [5] . Hence, various biological antioxidant assays were conducted to test the efficacy of biological active compounds found in chloroform and ethyl acetate fractions by comparing the results of DPPH, ABTS, H2O2 free radical scavenging activity upon the basis of the compounds nature.…”
Section: Discussionmentioning
confidence: 99%
“…and lipophilic antioxidant systems, while DPPH is only for hydrophobic systems). [5] Hence, various biological antioxidant assays were conducted to test the efficacy of biological active compounds found in chloroform and ethyl acetate fractions by comparing the results of DPPH, ABTS, H2O2 free radical scavenging activity upon the basis of the compounds nature.…”
Section: Chemistryselectmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancing beer with various flavonoids and other dietary supplements such as taurine, resveratrol, and caffeine has increased its nutritional value [ 14 ]. The common bean ( Phaseolus vulgaris ) has been shown to have significant anti-obesity potential due to its high phenolic content and antioxidant effects, exhibiting significant effectiveness against fat formation and insulin resistance [ 15 ]. According to recent studies, many food wastes, especially the byproducts of vegetables and fruits, are an excellent source of bioactive substances that may be isolated and added to food as natural food additives or used as complex matrices to create nutraceuticals and functional meals [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although various biological activities have been identified in various Sargassum species, little is known about the properties of S. macrocarpum . According to a previous study, the two Italian varieties of common bean showed a potent antioxidant activity and anti-inflammatory activity depending on the concentration of the major phenols in them [ 19 ]. In addition, another study reported that the extracts of A. macrostachyum , H. portulacoids , and S. europaea showed different enzyme inhibition effects, with different total phenols and flavonoids depending on the extraction method [ 20 ].…”
Section: Introductionmentioning
confidence: 99%